Hello, Goodbye - David, Lloyd, author 561446; Palmer, Meg, illustrator 563378 (London : Walker Books Ltd., 1983)
Hello, Goodbye A tree stood quietly in the sunshine. A big brown bear stepped up. "Hello!" he said, very loudly. "Hello! Hello!" come little voices, squeaky voices and deep-down voices from all over the tree. But when it begins to rain, what do you think they say? Full description.